Intramolecular H-type dimer and excimer formation in dibenzoylmethanatoboron difluoride dyads connected via diphenylsiloxane linkers. (December 2022) - Belova, Anastasia S.; Kononevich, Yuriy N.; Ionov, Dmitry S.; Sazhnikov, Viacheslav A.; Volodin, Alexander D.; Korlyukov, Alexander A.; Dorovatovskii, Pavel V.; Alfimov, Mikhail V.; Muzafarov, Aziz M.
Abstract: A series of new dibenzoylmethanatoboron difluoride (DBMBF2 ) and methoxy-substituted DBMBF2 dyads linked via flexible diphenylsiloxane linkers of various length have been synthesized and characterized. The structure and optical properties of these compounds were studied by X-ray single-crystal measurements, electron absorption, and steady-state and time-resolved fluorescence spectroscopy. In the dyads under study, which are in an equilibrium between the open and folded conformations, the formation of intramolecular H-dimers in the ground state are observed. For the dyads in dilute solutions in various solvents, both monomer and excimer (through intramolecular excimer formation) emissions are observed at room temperature. The effect of solvent polarity and linker length on the formation of intramolecular excimers has been studied. The contribution of excimers into the total fluorescence spectrum decreases with increasing the solvent polarity, and the length of the siloxane linker. The studied dyads in hexane and cyclohexane solutions have CIE chromaticity coordinates very close to the white color point. The mechanofluorochromic properties of the synthesized dyads were studied. Graphical abstract: Image 1 Highlights: A series of new dibenzoylmethanatoboron difluoride dyads were synthesized. The structure and optical properties of the dyads were studied. The formation of intramolecular H-dimers in the ground state are observed. For the dyads in dilute solutions both monomer and excimer emissions are observed. The dyads have CIE chromaticity coordinates very close to the white color point.